2018
DOI: 10.1007/s10236-018-1134-z
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal variation in lateral trapping of fine sediment in tidal estuaries: observations and a 3D exploratory model

Abstract: This study investigates the longitudinal variation of lateral entrapment of suspended sediment, as is observed in some tidal estuaries. In particular, field data from the Yangtze Estuary are analysed, which reveal that in one cross-section, two maxima of suspended sediment concentration (SSC) occur close to the south and north sides, while in a cross-section 2 km downestuary, only one SSC maximum on the south side is present. This pattern is found during both spring tide and neap tide, which are characterised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Cross‐sectional flows influence the salinity, leading to an intratidal salinity variation (ISV). Many studies have identified the salinity's response to the longitudinal and vertical process (Bowen, ; Chen & de Swart, ; Dyer, ; Simpson et al, ). However, few observations directly relate salinity fluctuations to lateral flows.…”
Section: Introductionmentioning
confidence: 99%
“…Cross‐sectional flows influence the salinity, leading to an intratidal salinity variation (ISV). Many studies have identified the salinity's response to the longitudinal and vertical process (Bowen, ; Chen & de Swart, ; Dyer, ; Simpson et al, ). However, few observations directly relate salinity fluctuations to lateral flows.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in the surface bottom, the velocity of current becomes weaker ranging from -0.3-0.4 m/s caused by the many factors such as bottom friction, the higher value of density, and some other forces (Van Rijn, 2011). If we see in more detail, the tidal ellipses that rotate counterclockwise bottomward show the influence of Coriolis forces (Chen & de Swart, 2018). This event also determines that the Ekman spiral principal controls the vertical transport that occurred in Sabang Bay.…”
Section: Hydrodynamic Characteristicsmentioning
confidence: 85%
“…On the other hand, during 20-year tidal prediction, we also identified the lowest water level during spring tidal conditions of 1.86 meters beneath MSL, while, the average minimum surface level during spring tidal conditions is 1.34 meters, with the lowest value of 0.91 meters beneath MSL. The variability of surface elevation changes has a role in generating surface currents and transport mechanisms in the estuarine area (Chen & de Swart, 2018). The higher the elevation formed, the more substantial transport energy resulted from this tidal fluctuation (Qarnain et al, 2014).…”
Section: Hydrodynamic Characteristicsmentioning
confidence: 99%
“…The lateral flow asymmetry in the North Passage results from lateral density gradients and the curvature effect (Chen and de Swart, 2018;Zhu et al, 2018;Zhou et al, 2019). Due to the lateral flow asymmetry, the CBS pool tends to move to the south flank of the channel, especially when sediment settles from the CBS to the bed (Fig.…”
Section: Implications For Sediment Transportmentioning
confidence: 99%